Replay - Creech, Sharon (Joanna Cotler Books : HarperTrophy, 2007)
While preparing for a role in the school play, twelve-year-old Leo finds an autobiography that his father wrote as a teenager and ponders the ways people change. Includes the text for the play, "Rumpopo's Porch.".